THE LEARNING CURVE: AN APPLICATION IN TURKISH MANUFACTURING INDUSTRY - Gürkan Çalmaşur; Hüseyin Daştan; Zeynep Karaca (Innovative Issues and Approaches in Social Sciences, 2021)
The learning curves have traditionally been used for manufacturing industries. Manufacturing industry is the branch of industry in which raw materials are processed by machine or manual labor and converted into intermediate goods. The main aim of this article is to make a detailed analysis the learning curves in the Turkish manufacturing industry for 2003-2017 period. In order to satisfy this aim, the cubic learning model has been estimated and calculated the progress ratio values for 24 Turkish manufacturing industries from 2003 to 2017. As a result, between 2003 and 2017, total Turkish manufacturing industry has a convex learning curve.